Analisis Kualitas Produk, Harga Dan Citra Merek Terhadap Keputusan Pembelian Produk Air Minum Dalam Kemasan Merek Narmada (Konsumen Di Unter Iwes Kabupaten Sumbawa Besar) - Ardiansyah Ardiansyah; Muhammad Agus Salim; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of product quality, price and brand image on the decision to purchase Narmada bottled drinking water with the IBM SPSS version 21 program. The sample in this study amounted to 60 respondents who lived and had bought Narmada bottled drinking water products in the Unter Iwes sub-district. The data used in this study is multiple linear regression analysis using simultaneous and partial hypothesis testing with the results that simultaneously product quality, price, and brand image have a positive and significant effect on purchasing decisions. Partially, product quality and brand image have no positive and insignificant effect on purchasing decisions, while price has a positive and significant effect on purchasing decisions. Keywords: Product Quality, Price, Brand Image, Purchase Decisions.